Combinatorial delivery of Crizotinib–Palbociclib–Sildenafil using TPGS-PLA micelles for improved cancer treatment - Diogo, Duarte Miguel de Melo (2018)
The co-delivery of multiple chemotherapeutics by micellar delivery systems is a valuable approach to improve cancer treatment since various disease hallmarks can be targeted simultaneously. However, the delivery of multiple drugs requires a nanocarrier structure that can encapsulate various bioactive molecules. In this study, we evaluate the simultaneous encapsulation of a novel triple drug combination in D-α-tocopheryl polyethylene glycol 1000 succinate-poly(lactic acid) (TPGS-PLA) amphiphilic micelles for cancer therapy. The drug mixture involves two anti-tumoral drugs, Crizotinib and Palbociclib combined with Sildenafil, a compound that is capable of increasing drug accumulation in the intracellular compartment. Such combination aims to achieve an enhanced cytotoxic effect in cancer cells. Our results demonstrated that TPGS-PLA copolymers self-assembled into stable nanosized micelles (158.3 nm) capable of co-encapsulating the three drugs with high loading efficiency. Triple drug loaded TPGS-PLA micelles were internalized in A549 non-small lung cancer cells and exhibited an improved cytotoxic effect in comparison with single (Crizotinib) or dual (Crizotinib–Palbociclib) drug loaded micelles, indicating the therapeutic potential of the triple co-delivery strategy. These findings demonstrate that TPGS-PLA micelles are suitable carriers for multiple drug delivery and also that this particular drug combination may have potential to improve cancer treatment.